Plan de Negocios para la producción y comercialización de cobertores para colchones en tela antifluida, para la empresa Confecciones Jossy Sport en la cuidad de Loja - Cueva Martínez, Lastenia Lizzette (2022)
The feasibility for the production and commercialization of mattress covers in the city of Loja resulted in an effective demand of 29,516 mattress covers, a supply of 5,592, obtaining an unsatisfied demand of 23,924 units: within the technical study, 80% of the installed capacity was considered, which corresponds to 5,255 units, covering 21.46% of the market share. Through this section, it was also determined the size, engineering of the project, the organizational and functional structure, since the company is legally constituted, it will run with its own capital , thus, an economic study determined an investment of $12,601.11, as well as the budgets of income and costs. The financial evaluation, which are based on a Net Present Value (NPV) of USD 36. 125.54 being a positive NPV, exceeding the initial investment: an Internal Rate of Return (IRR) 76.81%, which means that this percentage is higher than the opportunity cost; the investment will be recovered in 2 years, 6 months and 25 days: According to the benefit/cost ratio the company will obtain a profitability of $ 0.19 cents for each US dollar invested, finally the sensitivity analysis determines that the project will support an increase in costs 10.40% and a decrease in income 8.90% . Therefore, the respective financial analysis of the project is profitable and viable for its execution. It is worth mentioning that the type of research was descriptive, for which research methods, techniques and instruments were used to analyze, collect and interpret the information